An investigation into taxpayer consciousness of their marginal income tax rates - Huang, Jie (2008)
This research paper investigates the level of marginal income tax rate consciousness of taxpayers in Singapore. It was hypothesized in this paper that (1) the general Singapore population will tend to overestimate their marginal income tax rate, (2) higher income will lead to higher probability of an individual over or underestimating his marginal income tax rate, and (3) 8 identified factors have significant impact in explaining the difference in the level of marginal income tax rate consciousness.